2007
DOI: 10.1111/j.1600-0404.2007.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine without aura: comparison with cervicogenic headache. Vågå study of headache epidemiology

Abstract: MwoA and CEH have clearly different characteristics. The differences between MwoA and CEH are staggering. It is unlikely that migraine and CEH are linked in a nosological sense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 14 publications
3
31
0
2
Order By: Relevance
“…For TTH, the prevalence of 40% (RR 3.4) in JME is also significantly higher than expected from our control population [19], but it is similar to the numbers reported elsewhere (34% in [20], 38% in [21]). The data in the literature on headache in epilepsy are in line with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…For TTH, the prevalence of 40% (RR 3.4) in JME is also significantly higher than expected from our control population [19], but it is similar to the numbers reported elsewhere (34% in [20], 38% in [21]). The data in the literature on headache in epilepsy are in line with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…It is interesting to note that migraine appeared to have little effect in this study on CGH pain and disability outcomes for the longitudinal profile (data not shown). This may be attributed to independence of mechanisms [55-57] or the influence of treatment observed in the study on “other” headaches (migraine and/or tension-type). A clinical benefit for SMT in the treatment of all 3 headache types has been noted in systematic reviews [15-17,19,58].…”
Section: Discussionmentioning
confidence: 99%
“…However, TTH much less commonly will present as a differential challenge to the physician because the pain here tends to be bilateral and the symptoms and signs of neck involvement are lacking. CEH traits are typically not present in TTH [46]. In our series, out of the 19 CEH CHISG criteria, TTH patients fulfilled 4.89±1.57 (CH patients: 10.51±2.14, P=0.0001).…”
Section: Ceh Without Migrainous Traits If a Cervical Lesionmentioning
confidence: 78%
“…CEH prevalence may reach 4.1% [16]. The female preponderance once believed to be marked [17][18][19] may not be too relevant [20]. CEH starts early or late in life, frequently following migraine or tension-type headache (TTH).…”
Section: Clinical Picture Of Cehmentioning
confidence: 99%